Financial market integration, arbitrage and interest rate parity in the Caribbean - Seerattan, Dave (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Reviews the arbitrage opportunities available in the short end of the money markets of Guyana, Jamaica and Trinidad and Tobago, the degree of convergence between foreign interest rates and domestic rates in these countries using the framework of the Uncovered Interest Parity (UIP) and the decomposition of the factors that drive interest parity or the lack therof.